Novel Flp pilus biogenesis-dependent natural transformation - Angelov, Angel; Bergen, Paul; Nadler, Florian; Hornburg, Philipp; Lichev, Antoni; Übelacker, Maria; Pachl, Fiona; Kuster, Bernhard; Liebl, Wolfgang (Frontiers in Microbiology, 2015)
Natural transformation has been described in bacterial species spread through nearly all major taxonomic groups. However, the current understanding of the structural components and the regulation of competence development is derived from only a few model organisms. Although natural transformation was discovered in members of the Actinobacteria (high GC Gram-positive bacteria) more than four decades ago, the structural components or the regulation of the competence system have not been studied in any representative of the entire phylum. In this report we identify a new role for a distinct type of pilus biogenesis genes (tad genes, for tight adherence), which so far have been connected only with biofilm formation, adherence and virulence traits. The tad-like genes found in the genome of Micrococcus luteus were shown to be required for genetic transformation in this actinobacterial species. We generated and analysed individual knockout mutants for every open reading frame of the two predicted tad gene clusters as well as for a potential prepilin processing peptidase and identified the major component of the putative pili. By expressing a tagged variant of the major prepilin subunit and immunofluorescence microscopy we visualized filamentous structures extending from the cell surface. Our data indicate that the two tad gene islands complementarily contribute to the formation of a functional competence pilus in this organism. It seems likely that the involvement of tad genes in natural transformation is not unique only for M. luteus but may also prove to be the case in other representatives of the Actinobacteria, which contains important medically and biotechnologically relevant species.